Arteriovenous fistulas for chronic hemodialysis - Campos Pierri, Néstor; Campos Pierri, Néstor; Boucq, Richard (Cirugía del Uruguay, 1993)
The author reports the experience from the Diagnosis Center of the Medico-Surgical Society in Salto from 1987 to 1991, and analyses 75 angioacceses far chronic hemodialysis in 41 patients. This sample is analised, as we/1 as the type of arterio-venous fistulas that were made and their complications.